Nonreciprocal unconventional photon blockade in a spinning microwave magnomechanical system - Rui Hou; Wei Zhang; Xue Han; Hong-Fu Wang; Shou Zhang (Scientific Reports, 2025)
Abstract We propose a method for realizing the nonreciprocal unconventional photon blockade (NUPB) effect in a spinning microwave magnomechanical system. We determine the optimal parameter conditions for achieving this effect and observe that the numerical solutions are in excellent agreement with the analytical results. Under these optimal conditions, driving the system from the right induces photon antibunching, while driving from the left with identical amplitude leads to photon bunching. This pronounced asymmetry gives rise to NUPB, which arises from the combined effects of destructive quantum interference in two-photon excitation pathways and the Sagnac effect. Furthermore, NUPB can be tuned by adjusting the angular velocity of the microwave resonator. This work provides significant theoretical support for the realization of nonreciprocal single-photon sources and opens new avenues for the design and application of nonreciprocal quantum devices.